2022
DOI: 10.1371/journal.pone.0273485
|View full text |Cite
|
Sign up to set email alerts
|

Double burden of malnutrition in Nepal: A trend analysis of protein-energy malnutrition and High Body Mass Index using the data from Global Burden of Disease 2010–2019

Abstract: Background The co-existence of undernutrition and overnutrition is a global public health threat. We aim to report the burden of both nutritional deficiency (Protein-Energy Malnutrition) and overweight (high Body Mass Index) in Nepal over a decade (2010–2019) and observe the changes through trend charts. Methods We did a secondary data analysis using the Institute for Health Metrics and Evaluation (IHME)’s Global Burden of Disease (GBD) database to download age-standardized data on Protein Energy Malnutritio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…AdamW handles weight decay more effectively than Adam and RMSProp. Figures 4,6 In Figures 10, 11, and 12, it is evident that the misclassification rates for learning rates 0.1, 0.01, and 0.001 are notably higher when compared to the misclassification rate associated with a learning rate of 0.0001 for the Adamax, AdamW, and RMSprop optimizers. Specifically, when utilizing a learning rate of 0.0001, ResNet-18 misclassifies 62, 54, and 57 instances with the Adamax, AdamW, and RMSprop optimizers, respectively, resulting in misclassification rates of 13.77%, 10.8%, and 12.52%.…”
Section: Classification Using Resnet-18mentioning
confidence: 96%
See 2 more Smart Citations
“…AdamW handles weight decay more effectively than Adam and RMSProp. Figures 4,6 In Figures 10, 11, and 12, it is evident that the misclassification rates for learning rates 0.1, 0.01, and 0.001 are notably higher when compared to the misclassification rate associated with a learning rate of 0.0001 for the Adamax, AdamW, and RMSprop optimizers. Specifically, when utilizing a learning rate of 0.0001, ResNet-18 misclassifies 62, 54, and 57 instances with the Adamax, AdamW, and RMSprop optimizers, respectively, resulting in misclassification rates of 13.77%, 10.8%, and 12.52%.…”
Section: Classification Using Resnet-18mentioning
confidence: 96%
“…The Puskesmas Ubung dataset was used to test the model [16]. A decision tree that made use of the Gini index metric was created in order to address problems associated with Protein-Energy Malnutrition (PEM), which results in stunting, wasting, and underweight in babies [6].…”
Section: A Deep Learning Approach For Malnutrition Detectionmentioning
confidence: 99%
See 1 more Smart Citation
“…These effects of globalization may slow progress in reducing undernutrition while increasing risk factors for overnutrition. Malnutrition in this study refers to thinness, and DBM has now been identified in many developing countries ( 5 9 ), including China, and it is critical to explore the current state of development and the drivers of DBM.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, attention to the nutritional statuses of school-aged children and adolescents and the imposition of appropriate interventions are essential for their healthy transition to adulthood. Thinness was associated with premature mortality, physical suboptimal health, impaired neurocognitive function, and low productivity ( 9 11 ), and mortality and morbidity were 9–11 times higher in children with severe malnutrition than in well-nourished children ( 12 ); obesity in children and adolescents was associated with the development of ischemic heart disease ( 13 ), type II diabetes, respiratory disease, and psychological and social problems ( 14 , 15 ) and had a strong tracking effect in adulthood ( 16 ). In addition, lifestyle changes such as less sleep time and physical activity and longer screen time in children and adolescents have been reported worldwide in recent years ( 17 20 ) and have played a negative role in the prevention and control of overweight and obesity.…”
Section: Introductionmentioning
confidence: 99%